THE ROLE OF INTERNAL CONTROL SYSTEMS AND BEHAVIORAL ACCOUNTING ON THE EFFECTIVENESS OF PHILANTHROPIC FUND COLLECTION IN NORTH SUMATRA: MODERATION OF AMIL BEHAVIOR - Armansyah; Maya Sari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of internal control and behavioral accounting on the effectiveness of philanthropic fundraising, with amil behavior as a mediating variable. This study uses a quantitative approach with a survey method, where data are analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The test results indicate that internal control and behavioral accounting have a positive and significant effect on the effectiveness of philanthropic fundraising. In addition, both variables also have a significant effect on amil behavior. The results of the indirect effect test prove that amil behavior is able to significantly mediate the relationship between internal control and behavioral accounting on the effectiveness of philanthropic fundraising. This finding confirms that the effectiveness of philanthropic fundraising is not only determined by organizational systems and procedures, but is also greatly influenced by the behavior of amil as the main implementer of fundraising activities.